Temperature acclimation of leaf respiration differs between marsh and mangrove vegetation in a coastal wetland ecotone. (27th October 2021) - Sturchio, Matthew A.; Chieppa, Jeff; Chapman, Samantha K.; Canas, Gabriela; Aspinwall, Michael J.
Abstract: Temperature acclimation of leaf respiration ( R ) is an important determinant of ecosystem responses to temperature and the magnitude of temperature‐CO2 feedbacks as climate warms. Yet, the extent to which temperature acclimation of R exhibits a common pattern across different growth conditions, ecosystems, and plant functional types remains unclear. Here, we measured the short‐term temperature response of R at six time points over a 10‐month period in two coastal wetland species ( Avicennia germinans [C3 mangrove] and Spartina alterniflora [C4 marsh grass]) growing under ambient and experimentally warmed temperatures at two sites in a marsh–mangrove ecotone. Leaf nitrogen (N) was determined on a subsample of leaves to explore potential coupling of R and N. We hypothesized that both species would reduce R at 25°C ( R 25 ) and the short‐term temperature sensitivity of R ( Q 10 ) as air temperature ( T air ) increased across seasons, but the decline would be stronger in Avicennia than in Spartina . For each species, we hypothesized that seasonal temperature acclimation of R would be equivalent in plants grown under ambient and warmed temperatures, demonstrating convergent acclimation. Surprisingly, Avicennia generally increased R 25 with increasing growth temperature, although the Q 10 declined as seasonal temperatures increased and did so consistently across sites and treatments. Weak temperature acclimation resulted in reduced homeostasis of R in Avicennia . Spartina reduced R 25 and the Q 10 as seasonal temperatures increased. In Spartina, seasonal temperature acclimation was largely consistent across sites and treatments resulting in greater respiratory homeostasis. We conclude that co‐occurring coastal wetland species may show contrasting patterns of respiratory temperature acclimation. Nonetheless, leaf N scaled positively with R 25 in both species, highlighting the importance of leaf N in predicting respiratory capacity across a range of growth temperatures. The patterns of respiratory temperature acclimation shown here may improve the predictions of temperature controls of CO2 fluxes in coastal wetlands. Abstract : We repeatedly measured the short‐term temperature response of leaf respiration ( R ) over a 10‐month period in Avicennia germinans and Spartina alterniflora growing under ambient and warmed temperature treatments at two sites in a marsh–mangrove ecotone. In each species, we tested whether temperature acclimation of R is consistent over seasons, sites, and treatments. Avicennia showed little evidence of temperature acclimation. Spartina showed temperature acclimation of R that was consistent across seasons, sites, and treatments. Leaf nitrogen scaled positively with respiratory capacity in both species. These results could aid predictions of carbon fluxes from coastal wetlands under current and future climate conditions.